DECREASE OF CRACK-FORMATION IN LOW-CARBON CONSTRUCTIONAL HIGH-QUALITY BAR OF THE CONTINUOUSLY CAST SLUG - S. M. Borschov; V. A. Lutsenko; T. N. Golubenko; I. A. Kovalyova; A. V. Vengura; A. N. Hodosovskaya; V. I. Gritsaenko (Литьë и металлургия)
Features formation of cracks in steel 18хГТ are investigated. It is established that in the course of crystallization the peritectic transformation goes on phase reactions: formation of primary ferrite from liquid and formation of peritectic austenite from this ferrite and residual liquid.